Omental desmoplastic small round cell tumor with metastasis - Raghav Yelamanchi; Ekta Yadav; Nikhil Gupta; Arvind Ahuja; D S Chauhan (Wolters Kluwer Medknow Publications, 2022)
Desmoplastic small round cell tumor (DSRCT) is a very rare diagnosis with about 200 cases reported in literature. DSRCT is a recently described histopathological entity by Gerald and Rosai in 1989. Abdominopelvic cavity especially peritoneum is the most common site. We report a case of a huge omental DSRCT with lymph node metastasis which was initially misdiagnosed as gastrointestinal stromal tumor on radiology. A 26-year-old male presented with complaints of upper abdominal swelling associated with constant dull pain. On examination there was a large 15 × 12 cm intraabdominal mass in the epigastric and umbilical region. Imaging studies were suggestive of neoplastic mesenchymal etiology. Image-guided fine-needle aspiration cytology (FNAC) was suggestive of mesenchymal neoplastic etiology. On laparotomy, there was a huge 20 × 15 cm mass arising from omentum with multiple omental and mesenteric seedlings and mesenteric, peripancreatic and perigastric lymphadenopathy. The patient underwent debulking surgery with uneventful post-operative recovery. Histopathological examination with immunohistochemistry revealed a diagnosis of DSRCT of omentum and small bowel mesentery with lymph node metastasis. Patient then received adjuvant chemotherapy with multiple chemotherapeutic drugs as per P6 protocol and has stable disease at 1 year follow up.